Bioculturales, desde el principio: Una aproximación evolutiva al parto humano - Varea, Carlos (Avisos de Viena, 2024)
The study of human childbirth from the field of Biological Anthropology offers insights into the biocultural identity of our species. While reproduction is a biological process, its expression is shaped by cultural diversification across human groups, all aimed at ensuring maternal and offspring survival. Biological Anthropology, as a discipline, explores biological traits in human populations within a biocultural framework. The interplay between biology and culture defines our species, with cultural practices evolving alongside biological changes. The evolution of bipedalism and increased brain size in Homo species has influenced the complexity of human childbirth, necessitating adaptations in pelvic anatomy. Despite these adaptations, childbirth remains challenging, requiring assistance from others within the community, highlighting the universal role of midwives. The study of childbirth illuminates key evolutionary trends in our lineage, underscoring the intricate interplay between biological and cultural factors in shaping human reproductive experiences.